Conditions For Effective Human Resources Management Involving Remote Work In A Manufacturing Company - Joanna MICHALIK; Dorota WOJTYTO; Szymon BERSKI (Communications of International Proceedings, 2023)
The aim of the article is to present the factors that influence the quality of effective people management in a team. The characteristics of a "good" manager and the ways and techniques of his work and contact with employees were presented. Attention was drawn to the problems of remote work. Due to the relatively new situation in companies caused by the pandemic, this problem has not yet been sufficiently described in the literature, which makes this topic extremely important. The article also presents the results of a survey conducted in one of the manufacturing companies regarding the evaluation of managers by employees. Based on the obtained research results, it was found that the most important things for employees are responsibility, impartiality and adequate remuneration for the results achieved. Authority is important in a manager's work, as it influences the effectiveness of people management and increases the accuracy of decisions made. According to the respondents, having authority depends on the knowledge and skills of the manager, and it is strengthened by an objective approach, good organization and work planning.